Measurement of heat transfer coefficient in two phase flows of radiation-resistant zeotropic C2F6/C3F8 blends. (October 2017) - Doubek, M.; Haubner, M.; Vacek, V.; Battistin, M.; Hallewell, G.; Katunin, S.; Robinson, D.
Highlights: Addition of up to 25% of C2 F6 into a C3 F8 refrigerant effectively decreases the evaporation temperature. The heat transfer coefficient somewhat decreased with the progressive addition of C2 F6 . Various flow regimes in the horizontal evaporator are clearly visible from the obtained data. Abstract: We have measured the flow boiling heat transfer coefficient (HTC) of saturated fluorocarbon blends in a horizontal copper-nickel tube with a diameter of 4 mm. Direct (Joule) heating of the tube wall was used to obtain heat fluxes from 5 to 13.7 kW m −2 . Two different injection capillaries were used, permitting measurements at mass fluxes varying between 94 and 164 kg m −2  s −1 . The evaporation pressure was approximately 0.2 MPa for the mass fluxes close to 164 kg m −2  s −1 and 0.15 MPa for the lower mass fluxes. The same tube dimensions and material are used in the on-detector cooling channels of the silicon micro-strip charged particle tracker ("SCT") of the ATLAS experiment at the CERN Large Hadron Collider. The range of heat flux and mass flow studied encompasses the operating conditions of the tracker. When operating in the high radiation environment near to the proton beam collisions radiation tolerant coolants are essential. Saturated fluorocarbons (Cn F(2n+2) ) are radiation resistant and allow thermodynamic "tailoring" by blending saturated molecules of different orders. Measurements were made with pure C3 F8 (R218) and zeotropic blends containing 5, 10, 15, 20 and 25% (molar) C2 F6 (R116). This work is a continuation of a previous study which showed that the operating temperature of the ATLAS SCT could be reduced by around 10 °C with the admixture of 25% (molar) C2 F6, with no changes needed to the existing on-detector and circulatory pipework. The data analysis revealed multiple flow boiling regimes of the two-phase flow that varied as a function of coolant flow rate, heat flux, vapour quality and mixture composition. As expected, the HTC in pure C3 F8 was higher than in blends with increasing C2 F6 content. Nevertheless, the study confirmed that the ATLAS SCT could be operated at full power dissipation with cooling tube temperatures up to 10 °C colder than in pure C3 F8 with C3 F8/ C2 F6 blends having relatively modest values of HTCs in the range 1500–4000 W m −2  K −1 .